2014
DOI: 10.1002/jmrs.48
|View full text |Cite
|
Sign up to set email alerts
|

A survey of radiographers' confidence and self‐perceived accuracy in frontline image interpretation and their continuing educational preferences

Abstract: IntroductionThe provision of a written comment on traumatic abnormalities of the musculoskeletal system detected by radiographers can assist referrers and may improve patient management, but the practice has not been widely adopted outside the United Kingdom. The purpose of this study was to investigate Australian radiographers' perceptions of their readiness for practice in a radiographer commenting system and their educational preferences in relation to two different delivery formats of image interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 20 publications
2
56
1
Order By: Relevance
“…Additionally, a study published in 1997 comparing emergency doctors’ and untrained radiographers’ accuracy in identifying abnormal radiographs found comparable rates of detection (89% and 87% respectively) . Recent research into Australian radiographers’ confidence and self‐perceived accuracy in systems such as a PIE has shown an overall readiness to participate and, given the opportunity, further educate themselves to improve their image interpretation ability . The most effective method in which education is delivered to improve radiographic image interpretation warrants further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study published in 1997 comparing emergency doctors’ and untrained radiographers’ accuracy in identifying abnormal radiographs found comparable rates of detection (89% and 87% respectively) . Recent research into Australian radiographers’ confidence and self‐perceived accuracy in systems such as a PIE has shown an overall readiness to participate and, given the opportunity, further educate themselves to improve their image interpretation ability . The most effective method in which education is delivered to improve radiographic image interpretation warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recent research into Australian radiographers' confidence and selfperceived accuracy in systems such as a PIE has shown an overall readiness to participate and, given the opportunity, further educate themselves to improve their image interpretation ability. 28 The most effective method in which education is delivered to improve radiographic image interpretation warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic image interpretation is intricately linked to diagnosis, and as a result, radiographers have not historically been formally educated and trained in identifying and describing pathology on radiographs. This leaves a gap in their knowledge, skills and abilities, which leads to a lack of confidence 14. Furthermore, unequal power relationships may cause those positioned at the base of the hierarchical pyramid, such as radiographers, to remain silent 22…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, delay between radiographic image capture and the availability of the radiologist's report can contribute to missed, incomplete or incorrect diagnoses . One approach to mitigate risk and better support junior or inexperienced members of the referring clinical team is the recording of a brief comment by the radiographer at the time of image capture to highlight any abnormalities they may have detected …”
Section: Introductionmentioning
confidence: 99%
“…2,6,7 One approach to mitigate risk and better support junior or inexperienced members of the referring clinical team is the recording of a brief comment by the radiographer at the time of image capture to highlight any abnormalities they may have detected. [8][9][10][11] It has been suggested that radiographer commenting that highlights and describes acute abnormalities at the point of care may enhance patient management in hospital emergency departments. 10,[12][13][14] However, this enhancement is dependent on radiographers' ability to detect and describe abnormalities when viewing and interpreting trauma radiographs.…”
Section: Introductionmentioning
confidence: 99%